Ovarian Reservation in Women with Ovarian Endometriosis Cyst after Laparoscopic Cystectomy and Leuprorelin Acetate Administration: Cadangan Ovarium pada Perempuan dengan Kista Endometriosis Ovarium setelah Laparoskopi Kistektomi dan Leuprorelin Asetat - Yuli Trisetiyono; Soerjo Hadijono; Inu Mulyantoro; Ediwibowo Ambari; Reza F. Akhmad; I Edward K. Setiawan; Besari A. Pramono (Indonesian Journal of Obstetrics and Gynecology, 2023)
Objective: To determine differences in ovarian reserve in women with ovarian endometrial cysts after laparoscopic cystectomy and leuprorelin acetate administrationMethods: Single cohort prospective pre and post-test design study with 25 research subjects. The independent variables were interventional laparoscopic cystectomy, and leuprorelin acetate administration. The dependent variable is ovarian reserve as measured by AMH levels.Results: The research subjects had a mean age of 31 years and a BMI of 23.55 kg/m2. There were 8 subjects with unilateral cysts and 17 subjects with bilateral cysts. Preoperative AMH levels had a median value of 1.32 ng/mL (0.88-5.13), postoperative AMH levels had a median value of 1.07 ng/mL (0.60-4.53), and postoperative AMH levels + Leuprorelin Acetate injection had a median value of 1.06 ng/mL (0.50-4.65). There was a significant difference between preoperative AMH and postoperative AMH (p<0.001). There was no significant difference between postoperative AMH and postoperative AMH + Leuprorelin Acetate injection (p=0.149). BMI has a relationship (p=0.048) with pre-operative AMH levels with a weak and opposite relationship (r= -0.399).Conclusion: There was a statistically significant 18.9% decrease between pre-operative post-operative AMH levels. Body Mass Index (BMI) and pre-operative AMH levels are associated with one another.Keywords: anti-müllerian hormone, leuprorelin acetate, ovarian cystectomy, ovarian reserve.AbstrakTujuan: Mengetahui perbedaan cadangan ovarium pada perempuan dengan kista endometrium ovarium setelah laparoskopi kistektomi dan injeksi leuprorelin asetat.Metode: Desain penelitian pre dan post-test prospektif kohort tunggal dengan 25 subjek penelitian. Variabel bebas adalah intervensi laparoskopi kistektomi, dan injeksi leuprorelin asetat. Variabel terikat adalah cadangan ovarium yang diukur dengan kadar AMH.Hasil: Subjek penelitian memiliki rerata usia 31 tahun dan IMT 23,55 kg/m2. Terdapat 8 subjek dengan kista unilateral, 17 subjek dengan kista bilateral. Kadar AMH praoperasi memiliki nilai median 1,32 ng/mL (0,88-5,13), kadar AMH pascaoperasi memiliki nilai median 1,07 ng/mL (0,60-4,53), dan kadar AMH pascaoperasi + injeksi Leuprorelin Asetat memiliki nilai median 1,06 ng/mL (0,50-4,65). Ada perbedaan yang signifikan antara AMH pra operasi dan AMH pascaoperasi (p<0,001). Tidak ada perbedaan bermakna antara AMH pascaoperasi dengan injeksi AMH + Leuprorelin Asetat pascaoperasi (p=0,149). IMT memiliki hubungan (p=0,048) dengan kadar AMH pra operasi dengan hubungan yang lemah dan berlawanan (r= -0,399).Kesimpulan: Terdapat penurunan 18,9% antara tingkat AMH pra-operasi dan tingkat AMH pasca-operasi yang signifikan secara statistik. Ada hubungan antara BMI dan tingkat AMH pra-operasiKata kunci: cadangan ovarium, hormon anti-müllerian, kistektomi ovarium, leuprorelin asetat.